2008
DOI: 10.1002/jclp.20492
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of treatment research: does open access matter?

Abstract: Advocates of the Open Access movement claim that removing access barriers will substantially increase the diffusion of academic research. If successful, this movement could play a role in efforts to increase utilization of psychotherapy research by mental health practitioners. In a pair of studies, mental health professionals were given either no citation, a normal citation, a linked citation, or a free access citation and were asked to find and read the cited article. After 1 week, participants read a vignett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Whereas females and older providers have been more willing to use research findings, providers’ race/ethnicity has not been shown to relate significantly to their willingness to use research in practice. While research-related knowledge is not sufficient to compel providers to use research findings (Hardisty & Haaga, 2008), knowledge attained through, for example professional journals, has been shown to be associated with positive attitudes toward treatment guidelines for substance use disorders (Willenbring et al, 2004). Two studies comparing providers with master’s and doctoral degrees found no difference in their use of EBPs (Nelson & Steele, 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas females and older providers have been more willing to use research findings, providers’ race/ethnicity has not been shown to relate significantly to their willingness to use research in practice. While research-related knowledge is not sufficient to compel providers to use research findings (Hardisty & Haaga, 2008), knowledge attained through, for example professional journals, has been shown to be associated with positive attitudes toward treatment guidelines for substance use disorders (Willenbring et al, 2004). Two studies comparing providers with master’s and doctoral degrees found no difference in their use of EBPs (Nelson & Steele, 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…OA accelerates the uptake of information [32]. OA reaches more readers than subscription publishing with 23% more visitors, and 89% more full text and 42% more PDF downloads according to a bibliometric randomised controlled trial (RCT) of 1619 research articles [33].…”
Section: Knowledge Translationmentioning
confidence: 99%
“…One study compared the diffusion impact of different levels of access to articles and found that twice as many mental health professionals read articles with free OA citations and five times as many demonstrated knowledge of the content than those given articles with less accessible types ofcitation [36].…”
Section: Diffusion Impactmentioning
confidence: 99%
“…Further, a study at an Ontario, Canada public health department noted that the ability to make evidence-based decisions required not only training, technological resources, and a receptive organizational culture but also the ability to access research (Peirson, Ciliska, Dobbins, & Mowat, 2012). However, an experimental study demonstrated that mental health practitioners were significantly more likely to read an article with relevant practice information when given a citation to an open access article rather than a citation for a paid access article or no citation (Hardisty & Haaga, 2008). To the extent that social work moves toward a scientific base, the same supports are needed (Rzepnicki et al, 2012).…”
Section: Open Access: Context Forms and Costsmentioning
confidence: 99%